The Efficiency of a Service Provider in A Pandemic - Kamila URBAŃSKA and Agnieszka PARKITNA (Communications of International Proceedings, 2021)
The paper undertakes considerations to verify the assumptions of the conceptual model of efficiency developed by Parkitna in 2020 and to test its validity on a group of small service enterprises under pandemic conditions. Quantitative research was based on deductive approach and was conducted in the first half of 2021 in Poland, qualitative research was conducted in Lower Silesia in June and July 2021. The research technique used was the GOOgle electronic survey questionnaire and the collected data was statistically processed (SPSS). A sample was used in the study to select a set of population elements and establish the representativeness of the research sample. The theses and hypotheses presented were verified based on data collected in a quantitative study. The specificity of the distributions of the variables was established. Nonparametric tests were used to analyze the data. Correlations between variables were examined using Spearman's test.The verification of the research hypotheses confirmed the veracity of the Parkitna model of 2020. The assumptions made at the stage of selecting the research sample, allow to formulate a thesis of wider universality of the confirmed regularities, which should be confirmed in extended research. Which is an important contribution to further discussion.
Keywords: Efficiency; Services; Efficiency Model